Laser Powder Bed Fusion: A Review on the Design Constraints. Issue 1 (February 2021) - Ceccanti, F; Giorgetti, A; Arcidiacono, G; Citti, P
Abstract: With the creation of additive manufacturing production lines and the adoption of additive technologies, such as Laser Powder Bed Fusion, as standard manufacturing technologies for the mass production of parts, many considerations arise. In particular, product quality assurance is surely a very important aspect to be considered when talking about mass production. Laser powder bed fused parts are characterized by specific characteristics, such as quite rough surfaces and internal cavities filled with powder after the part construction. The need to ensure part quality and the importance to guarantee quality to all the parts made within the production line highlights the need to design the part addressing all the criticalities resulting from the manufacturing process, in addition to the ones related to the operative conditions. In this work, the attention is placed on two important topics: part surface inspectability and part cleaning. In particular, part inspectability is a crucial aspect in determining part coherence with design specifications. Part production via LPBF puts interpretability issues in inspecting the parts. Part cleaning is a crucial topic as well. Part cleaning is related to the design of the part to guarantee a correct powder evacuation from all the internal channels and cavities. Within the work, problems will be defined and design guidelines will be proposed to manage these topics.